Development Of Reverse Engineering System For Generating 3d Cad Body From 2d Image_875008757 - Abdulqawi, Nur Ilham Aminullah (2017)
Reverse engineering has the potential to be integrated into remote manufacturing applications, based on the internet technology today. However, reverse engineering using common scan-based device requires the physical object and the data acquisition device such as 3D laser scanner to co-exist at the same location, unless the physical object is made transferable within the cyber space. Reverse engineering based on 2D image is one of the potential solution for implementing remote reverse engineering process because 2D image is transferable with cyber space. However, reverse engineering based on 2D image must produce high dimensional accuracy outputs as exact as possible similar to the actual physical object in order to be relevant to the manufacturing industry. This research focused on developing a system for implementing reverse engineering based on 2D image, together with some unique techniques such as data segmentation, computer image processing methods and data refinement that were included into the system. Then, verification on the system was performed based on the implementation on real case objects, and the dimensional accuracy of each produced result was numerically analysed for further discussions. The results showed that reverse engineering based on 2D image is possible to be similar to the actual objects at accuracy level of less than 0.4mm. The proposed system will be the starting point for remote reverse engineering application, and has the potential to be an alternative solution whenever there is no data acquisition device such as 3D scanner available on the spot. The originality of this research is on the system and methodology used for producing 3D results from 2D data. The proposed system is not just suitable for remote reverse engineering application, but also is valuable for low cost reverse engineering application as well.